Update Opportunistic Infections of the Central Nervous System in Patients with Iatrogenic Immunosuppression - Arendt, Gabriele; Maschke, Matthias (Neurology International Open, 2017)
Opportunistic infections of the central nervous system (CNS) with bacteria, parasites, fungi or viruses due to iatrogenic immunosuppression are of immense importance because of rising numbers of organ transplantations and immunomodulating treatments. Besides transplantation medicine, the most frequently involved medical subspecialties are dermatology (interferons, rituximab, fingolimod, among others), hematology/oncology (rituximab, among others), neurology (beta-interferon, glatiramer acetate, natalizumab, rituximab, teriflunomide, fingolimod, alemtuzumab, daclizumab, among others) and rheumatology (rituximab).In Europe, typical infections affecting the immunocompromised host are due to herpes viruses and, especially in immunomodulated patients, JC virus (JCV); frequently occurring fungi are Aspergillus fumigatus, Candida albicans and Cryptococcus neoformans. An important parasite is Toxoplasma gondii (TG). Typical bacterial infections of the immunocompromised patient are caused by Nocardia asteroides, Listeria monocytogenes and Mycobacterium tuberculosis.Modern diagnostic and therapeutic procedures will be described.
Keywords: Opportunistic infections; central nervous system (CNS); iatrogenic immunosuppression and immunomodulation; typical infectious bodies